Answer:
yeah i think so
Help please
Answer:
the answer would be x equal 2.4
Step-by-step explanation:
sorry for my bad handwriting
Use rules of inference to prove that the following conclusion follows from these hypotheses:
C : ∃x (p(x) ∧ r(x))
Clearly label the inference rules used at every step of your proof.
2. Consider the following hypotheses:
H1 : ∀x (¬C(x) → ¬A(x)) H2 : ∀x (A(x) → ∀y B(y)) H3 : ∃x A(x)
Use rules of inference to prove that the following conclusion follows from these hypotheses:
C : ∃x (B(x) ∧ C(x))
Clearly label the inference rules used at every step of your proof.
3. Consider the following predicate quantified formula:
∃x ∀y (P (x, y) ↔ ¬P (y, y))
Prove the unsatisfiability of this formula using rules of inference.
Answer:
See deductions below
Step-by-step explanation:
1)
a) p(y)∧q(y) for some y (Existencial instantiation to H1)
b) q(y) for some y (Simplification of a))
c) q(y) → r(y) for all y (Universal instatiation to H2)
d) r(y) for some y (Modus Ponens using b and c)
e) p(y) for some y (Simplification of a)
f) p(y)∧r(y) for some y (Conjunction of d) and e))
g) ∃x (p(x) ∧ r(x)) (Existencial generalization of f)
2)
a) ¬C(x) → ¬A(x) for all x (Universal instatiation of H1)
b) A(x) for some x (Existencial instatiation of H3)
c) ¬(¬C(x)) for some x (Modus Tollens using a and b)
d) C(x) for some x (Double negation of c)
e) A(x) → ∀y B(y) for all x (Universal instantiation of H2)
f) ∀y B(y) (Modus ponens using b and e)
g) B(y) for all y (Universal instantiation of f)
h) B(x)∧C(x) for some x (Conjunction of g and d, selecting y=x on g)
i) ∃x (B(x) ∧ C(x)) (Existencial generalization of h)
3) We will prove that this formula leads to a contradiction.
a) ∀y (P (x, y) ↔ ¬P (y, y)) for some x (Existencial instatiation of hypothesis)
b) P (x, y) ↔ ¬P (y, y) for some x, and for all y (Universal instantiation of a)
c) P (x, x) ↔ ¬P (x, x) (Take y=x in b)
But c) is a contradiction (for example, using truth tables). Hence the formula is not satisfiable.
Answer:
75 ft
Step-by-step explanation:
Here we are given a right angled triangle with a known angle of 20°, length of the hypotenuse to be 80 and we are to find the length of the base x.
For that, we can use the formula for cosine for which we need an angle and the lengths of base and hypotenuse.
So putting in the given values to get:
Therefore, the value of x is the closest to 75 ft.
The map (x, y) -> (x + 2, - y - 2) would map triangle ABC to a similar, but not congruent triangle.
What is triangle ?
A triangle is a closed two-dimensional figure with three straight sides and three angles. The sum of the angles in a triangle is always 180 degrees. The three sides can be of different lengths, and the three angles can also be of different measures. Triangles are important geometric shapes and are used in many fields, such as mathematics, engineering, and architecture.
To determine which transformation maps triangle ABC to a similar but not congruent triangle, we need to understand the characteristics of similarity and congruence in triangles.
Two triangles are congruent if they have the same shape and size, and their corresponding sides and angles are equal. Two triangles are similar if they have the same shape, but not necessarily the same size, and their corresponding angles are equal.
In the given answer choices, the transformation (x, y) -> (- y, - x) is a reflection over the line y = x, which means it reverses the position of x and y coordinates. This transformation does not preserve the angles of the triangle, and therefore does not result in a similar triangle.
The transformation (x, y) -> (-4x, -4y) is a dilation with a scale factor of 4, which means it increases the size of the triangle by a factor of 4. This transformation preserves the angles of the triangle, and therefore results in a similar triangle that is also congruent.
The transformation (x, y) -> (x + 2, - y - 2) is a translation that moves the triangle 2 units to the right and 2 units down. This transformation preserves the angles of the triangle, and therefore results in a similar triangle.
The transformation (x, y) -> (-y + 2, x + 2) is a rotation of 90 degrees counterclockwise around the point (2, -2). This transformation preserves the angles of the triangle, and therefore results in a similar triangle.
Therefore, the map (x, y) -> (x + 2, - y - 2) would map triangle ABC to a similar, but not congruent triangle.
To know more about triangle visit:
#SPJ1
Answer:
the answer is 9.879
The angle will a 35-ft. ladder make the horizontal if it reaches the sample spot is .
Given that,
A 30-ft. ladder makes an angle of 60 degrees with the horizontal.
We have to find,
The angle will a 35ft.ladder make the horizontal if it reaches the sample spot.
According to the question,
A 30-ft. ladder makes an angle of 60 degrees with the horizontal when it reaches a given spot on a wall.
h = 30sin60
Then, the angle will a 35-ft. ladder make the horizontal if it reaches the sample spot.
Hence, The angle will a 35-ft. ladder make the horizontal if it reaches the sample spot is
For more information about Trigonometry click the link given below.